SODIUM-POTASSIUM-CHLORIDE COTRANSPORT IN THE REGULATION OF VASCULAR MYOGENIC TONE - S. N. Orlov; S. V. Koltsova; Ya. D. Anfinogenova; L. V. Kapilevich; S. N. Gusakova; L. V. Smagliy; M. B. Baskakov; M. A. Medvedev (Бюллетень сибирской медицины, 2014)
The article discusses the data on the functioning of Na+,K+,2Cl– cotransport – the carrier providing electroneutral symport of sodium, potassium and chloride, as well as molecular mechanisms of the regulation and physiological significance of this carrier. We analyzed the novel data on involvement of ubiquitous isoform of Na+,K+,2Cl–cotransporter (NKCC1) in regulation of vascular smooth muscle contraction, and role of this carrier in the regulation of cell volume and intracellular chloride concentration.